As-cast high-strength and high-toughness nodular cast iron traction wheel and preparation method thereof

CN122913448APending Publication Date: 2026-10-16LANGXI HUAMAO MASCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611187033.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0010]针对现有球墨铸铁曳引轮难以兼顾高强度、高韧性及多部位性能均匀性的问题,本发明提供一种铸态高强韧球墨铸铁曳引轮及其制备方法,能够改善石墨形核和基体组织分布,降低不同部位及轴向两侧的硬度差异,并在铸态条件下提高曳引轮的强度、塑性和性能一致性

Benefits of technology

[0022]Compared to existing technologies, this invention combines in-mold inoculation with in-flow barium silicate inoculation to improve and maintain the effective nucleation ability of molten iron when poured into the mold, promoting the refinement of graphite spheroids and improving graphite distribution. By controlling the preparation time difference between the upper and lower coated sand shells, the temperature difference at corresponding positions, and the time from mold closure to pouring, the initial thermal state difference between the upper and lower molds is reduced, improving the cooling consistency of different parts of the rim, spokes, and hub, as well as both sides of the axial direction. At the same time, a staged cooling method that connects closed mold cooling with delayed sand drop after mold opening is adopted, so that a relatively concentrated ferrite buffer structure is formed in the graphite adjacent area, and a high proportion of pearlite is maintained in the matrix area between graphite. Thus, without subsequent heat treatment aimed at changing the overall matrix structure, the cast traction wheel has both high tensile strength and elongation after fracture, and reduces the hardness difference between different parts and both sides of the axial direction, improving the uniformity of the traction wheel's structure and properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913448A_ABST
    Figure CN122913448A_ABST
Patent Text Reader

Abstract

The application discloses a kind of as-cast high strength and toughness nodular cast iron traction wheel and preparation method thereof, belong to nodular cast iron casting technical field.The method controls nodular cast iron composition and the silicon content of basic iron liquid before spheroidizing treatment, adopts in-packet inoculation and silicon barium stream inoculation cooperation, and utilizes two sand box shell preparation units to prepare upper and lower coated sand shell respectively, controls shell preparation completion time difference, corresponding position temperature difference and box to pouring time.After pouring, first keep iron type closed cooling, then open iron type and delay shakeout, so that the coated sand layer attached to the surface of casting continues to cool with the casting.The obtained as-cast traction wheel, ferrite phase is relatively concentrated in the vicinity of graphite, and the matrix outside the region maintains a high proportion of pearlite, so as to give consideration to tensile strength, elongation after fracture and hardness uniformity of different parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ductile iron casting technology, and more specifically, relates to a cast high-strength and high-toughness ductile iron traction wheel and its preparation method. Background Technology

[0002] The traction sheave is a key load-bearing component in a traction elevator, transmitting driving force. During operation, it must withstand continuous contact loads from the wire rope or steel belt, alternating bending loads, and impact loads generated during start-up and shutdown. A traction sheave typically consists of a rim, spokes, and hub, with significant differences in cross-sectional thickness, structural shape, and heat dissipation conditions across these different parts. To ensure sufficient load-bearing capacity and reliability under long-term operating conditions, the material must not only possess high tensile strength and hardness but also maintain suitable plasticity, toughness, and consistency in microstructure and properties across different parts.

[0003] Ductile iron possesses advantages such as good casting formability, high vibration damping performance, and relatively low manufacturing cost, and has been widely used in the manufacture of load-bearing castings such as traction wheels. The mechanical properties of ductile iron are mainly influenced by its chemical composition, graphite spheroidization state, number of graphite spheroids, matrix structure, and casting cooling conditions. For ductile iron with a tensile strength reaching 900 MPa, it is usually necessary to increase the pearlite content or form a strengthened matrix through heat treatment. However, excessive pearlite content, coarse pearlite lamellae, or localized carbide formation can easily lead to increased hardness and decreased plasticity; conversely, excessive ferrite content or unreasonable distribution can result in insufficient strength. Therefore, how to coordinate the graphite, pearlite, and ferrite structures under as-cast conditions is a problem that needs to be solved in the manufacture of high-strength and high-toughness ductile iron traction wheels.

[0004] Iron mold sand casting involves forming a coating of sand of a certain thickness on the inner surface of a metal mold, combining the strong thermal conductivity of a metal mold with the adaptability of a sand mold to the cavity. Compared with ordinary sand casting, iron mold sand casting can increase the cooling rate of the casting and is beneficial for refining graphite and matrix structure. However, there are significant cross-sectional differences between the rim, spokes, and hub of a traction wheel, and the cooling conditions experienced by each part during the eutectic solidification stage and the subsequent eutectoid transformation stage are not the same. Thinner parts such as spokes cool faster, which can easily lead to insufficient graphite nucleation, increased carbide tendency, or excessively high hardness; thicker parts such as the rim and hub cool slower, which can easily lead to coarse graphite, graphite morphology degradation, and microstructure segregation. This can result in significant differences in the number of graphite spherules, pearlite content, and hardness in different parts of the traction wheel.

[0005] Existing technologies have been studied for the composition design, spheroidizing treatment, inoculation treatment, and iron mold sand coating process of as-cast high-strength ductile iron. For example, CN114892068A discloses an as-cast QT900-7 ductile iron part and its preparation method. Through iron mold sand coating casting, four inoculation processes, spheroidizing treatment, and production process control, the roundness of graphite and the matrix structure are improved to obtain as-cast ductile iron parts with a tensile strength of not less than 900 MPa and an elongation after fracture of not less than 7%.

[0006] For example, CN117385268B discloses a method for preparing as-cast ductile iron, which involves adding alloying or regulating elements such as Cu, Cr, Ni, Sn, Ba, and Bi, combined with processes such as batching, smelting, spheroidizing, multiple inoculation, and sand casting in iron molds to prepare as-cast QT900-6 ductile iron. This technology can improve the strength and production stability of ductile iron, but its material structure and properties are affected by a variety of alloying elements, trace regulating elements, and multi-stage processing conditions, resulting in numerous process variables.

[0007] The aforementioned existing technologies mainly improve the strength and plasticity of as-cast ductile iron through alloying, repeated inoculation, and overall casting process control. However, for traction wheels and other rotating castings with significant differences in the cross-sections of the rim, spokes, and hub, there is still room for further improvement. On the one hand, the graphite nucleation state formed by inoculation treatment decays with the residence time of the molten iron, and the solidification rate of different parts further amplifies the differences in the number and morphology of graphite nodules. On the other hand, the enhanced cooling of the casting by the mold not only affects the formation of graphite in the eutectic solidification stage but also affects the migration of carbon and the formation of ferrite and pearlite in the subsequent eutectoid stage. When the cooling effect is too strong or the duration is inappropriate, it is easy for thinner parts to form excessively high hardness or local carbides, while thicker parts may still have coarsening of the microstructure and fluctuations in properties.

[0008] Furthermore, existing processes typically control chemical composition, inoculation treatment, and cooling conditions separately, failing to adequately consider the continuous influence between the graphite structure formed during the eutectic solidification stage and the matrix structure formed during the eutectoid transformation stage. This makes it difficult to simultaneously achieve optimal graphite spheroidization quality, carbide control, pearlite strengthening, localized ferrite distribution, and uniform hardness across different areas. While heat treatment can adjust the matrix structure to some extent, it increases energy consumption, production cycle, and manufacturing costs, and may cause deformation of the traction sheave, increasing the difficulty of subsequent processing.

[0009] Therefore, the existing manufacturing process of high-strength ductile iron traction wheels still needs further improvement in order to enhance the controllability of graphite and matrix structures under as-cast conditions, reduce the differences in structure and hardness between the rim, spokes and hub caused by different cross-sectional dimensions and cooling conditions, and obtain better plasticity and overall performance stability while maintaining high tensile strength. Summary of the Invention

[0010] To address the problem that existing ductile iron traction wheels cannot simultaneously achieve high strength, high toughness, and uniform performance across multiple parts, this invention provides a cast high-strength and high-toughness ductile iron traction wheel and its preparation method. This method can improve graphite nucleation and matrix structure distribution, reduce hardness differences in different parts and on both sides of the axial direction, and improve the strength, plasticity, and performance consistency of the traction wheel under as-cast conditions.

[0011] To solve the above problems, the present invention adopts the following technical solution.

[0012] A method for preparing a cast high-strength and high-toughness ductile iron traction wheel includes the following steps: The basic molten iron is prepared and smelted. A rare earth magnesium-silicon ferroalloy is used to spheroidize the molten iron, and an inoculation process is performed in the ladle using a ferrosilicon inoculant. The resulting ductile iron, by mass percentage, comprises: C: 3.15%–3.25%, Si: 3.70%–3.80%, Mn: 0.10%–0.20%, Cu: 0.70%–0.80%, residual Mg: 0.035%–0.050%, residual RE: 0.005%–0.015%, P: not more than 0.05%, S: not more than 0.025%, Sn: not more than 0.015%, Cr: not more than 0.10%, with the balance being Fe and unavoidable impurities. RE represents the total amount of rare earth elements. During the casting process, the barium silicon inoculant is added to the molten iron along with the iron flow for in-flow inoculation; The molten iron, which has been inoculated by the flow, is poured into the iron mold covered with sand. The iron mold is kept closed for 11 to 15 minutes after the pouring is completed, so that the casting can undergo the first stage of cooling in the iron mold covered with sand. After opening the mold, temporarily suspend the sand removal process, allowing the coating sand layer still attached to the surface of the casting to continue cooling for 3-8 minutes before proceeding with the sand removal and subsequent cooling.

[0013] Preferably, the obtained ductile iron comprises, by mass percentage: C: 3.18%–3.22%, Si: 3.72%–3.77%, Mn: 0.12%–0.17%, Cu: 0.72%–0.77%, residual Mg: 0.038%–0.044%, residual RE: 0.006%–0.011%, P: not more than 0.035%, S: not more than 0.015%, Sn: not more than 0.010%, Cr: not more than 0.060%, with the balance being Fe and unavoidable impurities; According to the calculation based on CE = C + Si / 3, the carbon equivalent CE of the obtained ductile iron is 4.42% to 4.48%.

[0014] Preferably, the mass ratio of residual RE to residual Mg in the obtained ductile iron is 0.14 to 0.28; The rare earth magnesium silicon ferroalloy comprises, by mass percentage: Mg: 6.5%–7.5%, RE: 0.8%–2.0%, Ca: 1.0%–2.5%, Si: 40%–45%, Al: not more than 1.0%, with the balance being Fe and unavoidable impurities; the amount of rare earth magnesium silicon ferroalloy added is 0.75%–0.95% of the mass of the base molten iron.

[0015] Preferably, the Si content in the base molten iron before spheroidizing treatment is 3.05% to 3.25%. Si is introduced into the molten iron through rare earth magnesium ferrosilicon alloy, ferrosilicon inoculant used for in-laminate inoculation, and barium silicon inoculant used for in-flow inoculation, so that the Si content in the obtained ductile iron is 3.70% to 3.80%. The Si content in the obtained ductile iron is 0.45 to 0.70 percentage points higher than the Si content in the base molten iron before spheroidizing treatment.

[0016] Preferably, the ferrosilicon inoculant used for inoculation in the package comprises, by mass percentage: Si: 72%–80%, Ca: 0.5%–1.0%, Al: not more than 1.0%, with the balance being Fe and unavoidable impurities; The amount of ferrosilicon inoculant added is 0.16% to 0.24% of the mass of the base molten iron, with a particle size of 1 to 4 mm; the amount of barium silicon inoculant added is 0.07% to 0.10% of the mass of the base molten iron, with a particle size of 0.2 to 0.8 mm. The barium silicon inoculant accounts for 25% to 35% of the total mass of the ferrosilicon inoculant and the barium silicon inoculant. The time from the start of in-flow inoculation to the completion of casting is 30 to 60 seconds.

[0017] Preferably, the barium silicon inoculant comprises, by mass percentage: Si: 70%–75%, Ba: 2.0%–4.0%, Ca: 0.5%–2.0%, Al: not more than 2.0%, with the balance being Fe and unavoidable impurities.

[0018] Preferably, the upper coated sand shell and the lower coated sand shell are prepared by two sand box shell-making units respectively; Each sandbox shell-making unit includes a mold, a sandbox that can be snapped into the mold, and a sand-shooting plate set above the sandbox. Both sandbox shell-making units prepare coated sand shells with the sand-shooting plate positioned above the corresponding sandbox. After the shell is made, one of the sand boxes is flipped over and then combined with the other sand box so that the upper and lower coated sand shells together form the casting cavity. The time difference between the completion of shell making in the two sand box shell making units shall not exceed 3 minutes; before the shells are closed, the temperature difference between the corresponding temperature measurement positions on the upper and lower sand boxes corresponding to the wheel rim, wheel spokes and wheel hub shall not exceed 15℃; the time from the completion of the shell closure to the start of pouring shall not exceed 4 minutes.

[0019] Preferably, each sand-shooting plate is provided with a first sand-shooting hole group and a second sand-shooting hole group, wherein the average hole diameter of the sand-shooting holes in the first sand-shooting hole group is greater than the average hole diameter of the sand-shooting holes in the second sand-shooting hole group. The first set of sand-shooting holes corresponds to the shell-forming area corresponding to the rim and hub, and the second set of sand-shooting holes corresponds to the shell-forming area corresponding to the spokes. The temperature of the iron mold during shell making is 205-235℃, and the thickness of the coated sand layer is 5-7mm; the superheating temperature of the base molten iron is 1535-1550℃, the tapping temperature is 1490-1520℃, and the pouring temperature is 1405-1415℃.

[0020] A cast high-strength and high-toughness ductile iron traction sheave, comprising by mass percentage: C: 3.15%–3.25%, Si: 3.70%–3.80%, Mn: 0.10%–0.20%, Cu: 0.70%–0.80%, residual Mg: 0.035%–0.050%, residual RE: 0.005%–0.015%, P: not more than 0.05%, S: not more than 0.025%, Sn: not more than 0.015%, Cr: not more than 0.10%, with the balance being Fe and unavoidable impurities, wherein RE represents the total amount of rare earth elements; At each metallographic sampling location of the traction sheave rim, spokes, and hub, the graphite spheroidization rate is not less than 90%, the number of graphite spheroids is 160–300 / mm², and the free carbide area fraction is not higher than 0.5%. At each metallographic sampling location of the traction wheel rim, spokes and hub, the area fraction of pearlite in the matrix is ​​75% to 90%, the total area fraction of other matrix structures besides pearlite and ferrite is no more than 5%, and the remainder is ferrite.

[0021] Preferably, at each metallographic sampling location of the wheel rim, spokes, and hub, the ferrite area within the graphite adjacency region formed by extending 10 μm outward from the boundary of each graphite sphere accounts for more than 60% of the total ferrite area within that metallographic sampling location; and in the matrix region outside the graphite adjacency region, the pearlite area accounts for no less than 80% of the matrix region area. The tensile strength of the traction sheave shall not be less than 900 MPa, the elongation after fracture shall not be less than 6.0%, the average Brinell hardness of each hardness test area of ​​the rim, spokes and hub shall be 245-280 HBW 10 / 3000 and the difference between the maximum and minimum values ​​shall not be greater than 15 HBW, and the Brinell hardness difference between each corresponding test point located on both sides of the axial center plane of the traction sheave and symmetrical about the axial center plane shall not be greater than 10 HBW.

[0022] Compared to existing technologies, this invention combines in-mold inoculation with in-flow barium silicate inoculation to improve and maintain the effective nucleation ability of molten iron when poured into the mold, promoting the refinement of graphite spheroids and improving graphite distribution. By controlling the preparation time difference between the upper and lower coated sand shells, the temperature difference at corresponding positions, and the time from mold closure to pouring, the initial thermal state difference between the upper and lower molds is reduced, improving the cooling consistency of different parts of the rim, spokes, and hub, as well as both sides of the axial direction. At the same time, a staged cooling method that connects closed mold cooling with delayed sand drop after mold opening is adopted, so that a relatively concentrated ferrite buffer structure is formed in the graphite adjacent area, and a high proportion of pearlite is maintained in the matrix area between graphite. Thus, without subsequent heat treatment aimed at changing the overall matrix structure, the cast traction wheel has both high tensile strength and elongation after fracture, and reduces the hardness difference between different parts and both sides of the axial direction, improving the uniformity of the traction wheel's structure and properties. Attached Figure Description

[0023] Figure 1 Flowchart of the preparation method for high-strength and tough ductile iron traction wheels; Figure 2 This is a schematic diagram showing the structure and inspection locations of the traction sheave casting. Figure 2 (a) is a schematic diagram of the metallographic sampling location. Figure 2 (b) is a schematic diagram of the hardness testing area and axially symmetrical testing points; Figure 3 This is a structural diagram of the sandbox shell-making unit.

[0024] In the diagram: 1. Sand box shell making unit; 11. Equipment working platform; 12. Mold pad frame; 13. Mold; 14. Sand box; 15. Sand shooting plate; 151. Sand shooting hole; 4. Traction wheel casting; 41. Wheel rim; 42. Wheel spoke; 43. Wheel hub; 44. Axial center plane; 45. Wheel rim metallographic sampling position; 46. Wheel spoke metallographic sampling position; 47. Wheel hub metallographic sampling position; 48a. Wheel rim hardness testing area; 48b. Wheel spoke hardness testing area; 48c. Wheel hub hardness testing area; 49. Axial symmetrical measuring points. Detailed Implementation

[0025] The present invention will be further described below with reference to the accompanying drawings. The following embodiments are used to illustrate the technical concept, process, and microstructure formation mechanism of the present invention, and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the content of each element and the composition of the alloy material are all mass percentages.

[0026] In this invention, "cast state" refers to the traction wheel after casting, cooling, unpacking, and sand removal, without further heat treatments such as normalizing, annealing, quenching, or tempering that would alter its overall microstructure. Subsequent surface cleaning, shot blasting, or machining will not affect its cast state properties.

[0027] RE represents the total amount of rare earth elements. The residual Mg and residual RE in ductile iron composition refer to the Mg content and total rare earth element content detected in the traction wheel casting 4 after the molten iron has undergone spheroidizing treatment, inoculation treatment, casting, and solidification. In rare earth magnesium-silicon ferroalloys, RE represents the sum of the contents of each rare earth element in the alloy.

[0028] "Unpacking" refers to separating the upper and lower molds that are in the closed state, allowing the traction wheel casting 4 to escape the closed cooling state formed by the upper and lower molds. After unpacking, the traction wheel casting 4 can be taken out directly, or it can be lifted or transported after the upper and lower molds have been separated.

[0029] "Temporarily delaying sand removal" means that after opening the box, within a specified time, the coated sand will not be actively peeled off from the surface of the traction wheel casting by vibration, knocking, impact or other mechanical means. However, it does not rule out the possibility that some coated sand will naturally crack or fall off during the opening, lifting or transportation process.

[0030] "Attached coated sand layer" refers to a coated sand layer that remains attached to at least part of the surface of the traction wheel casting 4 in a layered, continuous sheet, or segmented continuous manner after the casting is removed from the mold. The attached coated sand layer is not required to maintain a complete and closed sand shell morphology, but does not include a state where only a small number of discrete sand particles are attached to the surface of the casting.

[0031] like Figure 1 As shown, the preparation process of high-strength and tough ductile iron traction wheels includes basic molten iron preparation and smelting, spheroidizing treatment and inoculation in the ladle, preparation of upper and lower coated sand shells, turning and closing the mold, in-flow inoculation and pouring, mold closure and cooling, opening the mold and temporarily delaying sand removal, sand removal and subsequent cooling.

[0032] This invention achieves coordinated control over the composition of ductile iron, residual spheroidizing elements, in-laminate inoculation and in-flow inoculation, the initial thermal state of the iron mold covered with sand, and the cooling path before and after unpacking. This allows the graphite nucleation state formed during the eutectic solidification stage to further influence the carbon migration path during the eutectoid transformation stage, thus balancing the strength, plasticity, and performance consistency of different parts of the traction wheel without overall heat treatment.

[0033] The ductile iron produced after spheroidizing treatment, in-laminate inoculation, and in-flow inoculation comprises, by mass percentage: C: 3.15%–3.25%, Si: 3.70%–3.80%, Mn: 0.10%–0.20%, Cu: 0.70%–0.80%, residual Mg: 0.035%–0.050%, residual RE: 0.005%–0.015%, P: not higher than 0.05%, S: not higher than 0.025%, Sn: not higher than 0.015%, Cr: not higher than 0.10%, with the balance being Fe and unavoidable impurities.

[0034] In a preferred embodiment, the resulting ductile iron comprises, by weight percentage: C: 3.18%–3.22%, Si: 3.72%–3.77%, Mn: 0.12%–0.17%, Cu: 0.72%–0.77%, residual Mg: 0.038%–0.044%, residual RE: 0.006%–0.011%, P: not higher than 0.035%, S: not higher than 0.015%, Sn: not higher than 0.010%, Cr: not higher than 0.060%, with the balance being Fe and unavoidable impurities.

[0035] Based on the formula CE = C + Si / 3, the carbon equivalent CE of ductile iron within the preferred composition range is 4.42% to 4.48%.

[0036] Carbon (C) is used to ensure the fluidity of molten iron and to provide a carbon source for graphite precipitation. When the C content is below 3.15%, the eutectic degree of molten iron decreases, and under the strong cooling effect of the iron mold with sand coating, the tendency for free carbides to form in relatively thin parts such as the spokes 42 increases. When the C content is above 3.25%, the possibility of graphite coarsening and morphological fluctuations in relatively thick parts such as the rim 41 and the hub 43 increases.

[0037] Si promotes graphitization and solid solution strengthening. Controlling the Si content to 3.70%–3.80% can improve the strength of the ferrite itself, allowing the ferrite surrounding the graphite spheres to maintain a certain load-bearing capacity while providing plastic buffering. When the Si content is too low, the solid solution strengthening of local ferrite is insufficient; when the Si content is too high, the embrittlement sensitivity of the high-silicon matrix and the tendency for graphite degradation in thicker areas increase.

[0038] Cu is used to stabilize pearlite. When the Cu content is 0.70%–0.80%, it can inhibit excessive ferritification in the matrix region between graphite spheres during subsequent cooling, thus maintaining a high proportion of pearlite in the corresponding region. If the Cu content is too low, the proportion of ferrite in the matrix is ​​prone to increase, affecting strength and hardness; if the Cu content is too high, it may excessively inhibit the formation of ferrite in the region adjacent to the graphite spheres, resulting in increased hardness and decreased plasticity.

[0039] Both Mn and Sn have pearlite stabilizing effects, while Cr, in addition to its pearlite stabilizing effect, also increases the tendency for carbide formation. This invention uses Cu as the main pearlite stabilizing element, while controlling Mn, Sn, and Cr within relatively low ranges to avoid excessive hardness, increased free carbides, or matrix embrittlement caused by the superposition of multiple pearlite stabilizing elements.

[0040] When the phosphorus content is too high, brittle phosphorus eutectic structures are easily formed at grain boundaries and end solidification regions; sulfur (S) will consume spheroidizing elements and reduce the stability of spheroidizing treatment, so the upper limits of the contents of phosphorus and sulfur should be controlled respectively.

[0041] Residual Mg is mainly used to maintain graphite spheroidization. When the residual Mg content is below 0.035%, spheroidization degradation is more likely to occur in thicker parts and end solidification regions; when the residual Mg content is above 0.050%, the tendency for inclusion formation, shrinkage, and graphite morphology fluctuations may increase.

[0042] Residual RE plays a role in purifying molten iron, reducing the influence of interfering elements, and assisting in stabilizing spheroidization. However, under conditions of high Si and thick cross-sections, a higher residual RE is not necessarily better. When the residual RE is too low, the molten iron's resistance to interference is insufficient; when the residual RE is too high, it may work in conjunction with high Si, local slow cooling, and solidification segregation, increasing the possibility of degraded graphite formation.

[0043] This invention controls the residual rare earth element (RE) to 0.005%–0.015% and the mass ratio of residual RE to residual Mg to 0.14–0.28. The residual Mg plays the main role in spheroidization, while the residual RE plays a role in purification and anti-interference at a lower level, thus avoiding the need to adjust the graphite morphology through a high amount of residual rare earth elements.

[0044] The base molten iron is spheroidized using a rare earth magnesium-silicon-iron alloy. The rare earth magnesium-silicon-iron alloy comprises, by mass percentage: Mg: 6.5%–7.5%, RE: 0.8%–2.0%, Ca: 1.0%–2.5%, Si: 40%–45%, Al: not more than 1.0%, balance being Fe and unavoidable impurities.

[0045] The amount of rare earth magnesium silicon iron alloy added is 0.75% to 0.95% of the mass of the base molten iron before spheroidizing treatment. The specific amount added can be adjusted within the above range according to the S content in the base molten iron, the spheroidizing treatment temperature, and the absorption rate of Mg and RE, so that the residual Mg and residual RE in the solidified traction wheel casting 4 reach the corresponding range.

[0046] The amounts of rare earth magnesium ferrosilicon alloy, ferrosilicon inoculant used in ladle inoculation, and barium silicon inoculant used in in-flow inoculation are all calculated based on the mass of the base molten iron before spheroidizing treatment.

[0047] The Si content in the base molten iron before spheroidizing treatment is 3.05%–3.25%. By introducing Si into the molten iron through rare earth magnesium-silicon ferroalloy, ferrosilicon inoculant, and barium silicon inoculant, the Si content in the final ductile iron reaches 3.70%–3.80%, which is 0.45–0.70 percentage points higher than the Si content in the base molten iron before spheroidizing treatment.

[0048] The Si content in the base molten iron, the amount of each treatment material added, and the corresponding Si yield should be selected accordingly, and the endpoints of each range should not be arbitrarily combined. When preparing the base molten iron, an incremental space should be reserved for the Si introduced by subsequent spheroidizing treatment, ladle inoculation, and in-flow inoculation to avoid the final Si content exceeding the set range, and at the same time, to avoid reducing the necessary amount of inoculant added due to limiting the final Si content.

[0049] After spheroidization, inoculation with a ferrosilicon inoculant is performed. The ferrosilicon inoculant comprises, by mass percentage: Si: 72%–80%, Ca: 0.5%–1.0%, Al: not more than 1.0%, with the balance being Fe and unavoidable impurities.

[0050] The amount of ferrosilicon inoculant added is 0.16% to 0.24% of the mass of the base molten iron, and the particle size is 1 to 4 mm. This particle size is conducive to the gradual dissolution of the ferrosilicon inoculant in the molten iron and the establishment of the basic inoculation state, reducing oxidation loss caused by excessively small particles, and also avoiding insufficient dissolution caused by excessively large particles.

[0051] The incubation process within the ladle gradually diminishes as the molten iron is transported, held, and poured. To supplement the effective nucleation conditions near the solidification stage, a barium silicate inoculant is used for in-flow incubation during the pouring process.

[0052] The barium silicate inoculant comprises, by weight percentage: Si: 70%–75%, Ba: 2.0%–4.0%, Ca: 0.5%–2.0%, Al: not more than 2.0%, with the balance being Fe and unavoidable impurities.

[0053] The amount of barium silicon inoculant added is 0.07% to 0.10% of the mass of the base molten iron, with a particle size of 0.2 to 0.8 mm. Fine-grained barium silicon inoculant can dissolve more quickly during the flow of molten iron, making the supplementary inoculation effect closer to the moment when the molten iron enters the mold and begins to solidify.

[0054] The actual added mass of the barium silicon inoculant accounts for 25% to 35% of the total actual added mass of the ferrosilicon inoculant and the barium silicon inoculant. The specific added amounts of the two inoculants are within their respective added amount ranges and simultaneously meet the above-mentioned mass ratios.

[0055] When the proportion of barium silicon inoculant is too low, its compensatory effect on inoculum degradation within the package is insufficient; when the proportion is too high, the basic inoculum effect within the package is relatively weakened, and the addition of fine-grained inoculant may increase oxide inclusions, unmelted particles, or local component fluctuations.

[0056] The time from the start of in-flow inoculation to the completion of casting is 30–60 seconds. In-flow inoculation can be carried out by continuous addition, quantitative delivery, or segmented addition along with the casting flow, so that the barium silicon inoculant enters the casting system with the molten iron flow and is added before the casting is completed.

[0057] like Figure 3 As shown, the sand box shell making unit 1 includes a working platform 11, a mold pad frame 12 set on the working platform 11, a mold 13 set on the mold pad frame 12, a sand box 14 that can be engaged with the mold 13, and a sand shooting plate 15 located above the sand box 14. The sand shooting plate 15 is provided with a plurality of sand shooting holes 151.

[0058] Figure 3 Only one sand box shell-making unit 1 is shown. In the actual shell-making process, two sand box shell-making units 1 are set up. The two sand box shell-making units 1 are used to prepare the upper coated sand shell and the lower coated sand shell, respectively. The two sand box shell-making units 1 can adopt the same basic structure, and the forming contours of their molds 13 are adapted to the upper and lower profiles of the traction wheel casting 4, respectively.

[0059] Both sand box shell-making units 1 are sand-shotting and curing with the sand-shooting plate 15 positioned above the corresponding sand box 14, so that the upper and lower coated sand shells are formed under the same sand-shooting direction and similar filling, heating and curing conditions.

[0060] After the shell is formed, one of the sand boxes 14 is flipped over and then joined with the other sand box 14, so that the upper and lower coated sand shells together form the casting cavity. The upper and lower coated sand shells are determined according to the final box-joining position, and do not mean that they are located on top and bottom respectively during the shell-making process.

[0061] The time difference between the completion of shell making in the two sand box shell making units 1 is no more than 3 minutes. Before closing the shell, with one of the sand boxes 14 completed and the two sand boxes 14 not yet closed, the temperature of the corresponding positions on the outer side of the upper and lower sand boxes 14 and the wheel rim 41, wheel spoke 42 and wheel hub 43 are measured within 2 minutes.

[0062] In the upper and lower sand boxes 14, the two temperature measuring positions corresponding to the wheel rim 41 form a set of corresponding positions, the two temperature measuring positions corresponding to the wheel spoke 42 form a set of corresponding positions, and the two temperature measuring positions corresponding to the wheel hub 43 form a set of corresponding positions. The temperature difference between each set of corresponding positions is no greater than 15℃.

[0063] The time from the completion of mold assembly to the start of pouring should not exceed 4 minutes, in order to reduce the possibility of the iron mold temperature dropping and the temperature difference between the upper and lower corresponding positions widening again during the waiting process.

[0064] The co-directional shell making of the two sand box shell making units 1, the control of the shell making completion time difference, and the control of the corresponding position temperature difference ensure that the upper and lower iron molds have similar initial thermal states when the molds are closed, thereby reducing the difference in microstructure and hardness between the two axial sides of the traction wheel casting 4 caused by the different initial temperatures of the molds.

[0065] Each sand-shooting plate 15 is provided with a first sand-shooting hole group and a second sand-shooting hole group. The average diameter of the sand-shooting holes 151 in the first sand-shooting hole group is larger than the average diameter of the sand-shooting holes 151 in the second sand-shooting hole group.

[0066] The first set of sand-shooting holes corresponds to the shell-forming areas of the rim 41 and hub 43, while the second set of sand-shooting holes corresponds to the shell-forming area of ​​the spoke 42. The shell-forming space and sand requirement are relatively large in the areas corresponding to the rim 41 and hub 43, so the first set of sand-shooting holes with a larger average aperture is used to improve the sand supply capacity in these areas. The shell-forming space is relatively thin in the area corresponding to the spoke 42, so the second set of sand-shooting holes with a smaller average aperture is used to reduce concentrated impact and localized accumulation of the coating sand.

[0067] The first and second sand-shooting hole groups are used to improve the filling integrity and coating thickness consistency of different shell formation areas, and reduce undesigned cooling differences caused by sand shortage, excessively thick or thin local shells.

[0068] The temperature of the iron mold during shell making is 205-235℃, preferably 215-225℃. If the iron mold temperature is too low, the curing speed of the coated sand and the strength of the sand shell will be insufficient; if the iron mold temperature is too high, the coated sand may cure too quickly before the filling is completed, resulting in premature shelling near the sand injection hole 151 or insufficient filling at the far end.

[0069] The thickness of the coated sand layer is 5-7 mm. If the coated sand layer is too thin, the integrity of the sand shell and the adhesion stability after opening the mold will be insufficient, and the cooling effect of the iron mold on the traction wheel casting 4 may be too strong; if the coated sand layer is too thick, the heat transfer resistance will increase, which will weaken the enhanced cooling effect of the iron mold in the eutectic solidification stage.

[0070] After the base molten iron is melted, it is heated to 1535–1550℃ for overheating treatment to fully melt the furnace charge and alloys and promote uniform composition of the molten iron. If the overheating temperature is too low, the conditions for homogenization of the molten iron and the floating of inclusions are insufficient; if the overheating temperature is too high, the oxidation of the molten iron, the burning off of spheroidizing elements, and the attenuation of the original nucleation conditions are aggravated.

[0071] The tapping temperature of the base molten iron is 1490–1520℃. After tapping, it undergoes spheroidizing treatment and inoculation in the ladle, and is then transferred and cooled before pouring to bring the pouring temperature to 1405–1415℃.

[0072] When the pouring temperature is below 1405℃, the fluidity of the molten iron decreases, the filling stability of parts far from the ingate or with complex structures decreases, and the barium silicon inoculant may not dissolve completely. When the pouring temperature is above 1415℃, the high-temperature residence time of the molten iron before solidification increases, the effective nucleation state formed by inoculation is easily weakened, and the tendency of graphite coarsening in thick parts may increase.

[0073] During the casting process, the molten iron flow is kept continuous and stable, and the barium silicon inoculant is added to the molten iron along with the flow, so that the barium silicon inoculant is evenly dispersed during the casting process, reducing the local inoculation differences caused by concentrated addition.

[0074] After the molten iron is poured into the iron mold covered with sand, the time of completion of pouring is used as the starting point for timing. The iron mold is kept closed for 11 to 15 minutes to allow the traction wheel casting 4 to undergo the first stage of cooling inside the iron mold covered with sand.

[0075] During the first stage of cooling, the iron mold continuously absorbs heat from the traction wheel casting 4 through the coated sand layer. The coated sand layer prevents the molten iron from being directly subjected to excessive quenching by the metal mold, while the iron mold enables the traction wheel casting 4 to achieve a cooling intensity higher than that of ordinary sand casting. This cooling condition is beneficial for shortening the eutectic solidification time and reducing the tendency for graphite coarsening and solidification segregation in thicker parts such as the rim 41 and hub 43.

[0076] When the closed-circuit cooling time is less than 11 minutes, the main cross-sections of the wheel flange 41 and the wheel hub 43 may not have formed a stable solidified structure. After the box is opened, deformation, cracks, changes in the position of shrinkage porosity, or unstable sand shell adhesion may easily occur.

[0077] When the closed-mold cooling time exceeds 15 minutes, the traction wheel casting 4 continues to cool down under the strong thermal conductivity boundary of the iron mold. This may compress the temperature range of the matrix transformation path that is subsequently adjusted by opening the mold and delaying the sand falling, thereby increasing the pearlite content and hardness and inhibiting the formation of ferrite in the vicinity of the graphite spheres.

[0078] After cooling in the closed mold for 11-15 minutes, open the mold. During the unpacking process, use a smooth parting and removal method to avoid actively applying strong vibrations or impacts to the coated sand shell, so that the coated sand remains attached to at least part of the surface of the traction wheel casting 4 in a layered, continuous sheet or segmented continuous manner.

[0079] After opening the mold, temporarily suspend the sand removal process, allowing the attached coated sand layer to continue cooling along with the traction wheel casting 4 for 3-8 minutes before proceeding with the sand removal and subsequent cooling.

[0080] Opening the mold allows the traction wheel casting 4 to detach from the strong thermal conductivity boundary formed by the iron mold. The attached coated sand layer retains a certain thermal resistance between the traction wheel casting 4 and the surrounding environment, allowing the traction wheel casting 4 to transition from the strong cooling state inside the iron mold to the air cooling state after the sand is removed.

[0081] When the sand-fall delay time is less than 3 minutes, the regulating effect of the attached coating sand layer on the subsequent matrix transformation is insufficient; when the sand-fall delay time exceeds 8 minutes, the cooling rate of the traction wheel casting 4 may be too low, leading to an increase in the total amount of ferrite or coarsening of the pearlite structure, affecting the strength and hardness stability.

[0082] After a pause of sand removal for 3–8 minutes, proceed with sand removal using vibration, tapping, or other conventional methods, and then allow the traction wheel casting 4 to cool naturally to room temperature. Do not immediately apply water spraying or forced air cooling after sand removal to avoid creating a significant cooling difference between the casting surface and interior.

[0083] This invention improves and maintains effective nucleation density through the combination of in-pouring inoculation and in-flow inoculation. In-pouring inoculation is used to establish the basic inoculation state, while in-flow inoculation of barium silicon near pouring is used to compensate for inoculation decline caused by transport and waiting, so that the molten iron still has a large number of effective nucleation particles when entering the mold cavity.

[0084] Iron-coated sand casting molds have higher thermal conductivity than ordinary sand molds when in a closed state. This can shorten the time that molten iron is in the eutectic solidification temperature range, so that the effective nucleation conditions formed by inoculation during flow can be preserved before solidification, and promote the formation of more graphite spheres that are smaller in size and more evenly distributed.

[0085] As the number of graphite spheres increases, the average distance between adjacent graphite spheres decreases. Consequently, during the subsequent eutectoid transformation, the average distance that carbon in austenite needs to migrate to the graphite spheres decreases accordingly.

[0086] If the strong thermally conductive boundary formed by the iron mold is maintained during the eutectoid transformation, the time for carbon to migrate to graphite is insufficient, and the matrix is ​​prone to develop towards high pearlite and high hardness. If the cooling rate is too low or the slow cooling time is too long, ferrite may continue to expand from the vicinity of graphite spheres to the area between graphite spheres, resulting in a reduction in the pearlite bearing area.

[0087] In this invention, after the iron mold is closed and cooled for 11-15 minutes, it is opened, and the cooling continues for another 3-8 minutes using the coating sand layer still attached to the surface of the traction wheel casting 4. This transitional cooling condition provides time for carbon near the graphite spheres to migrate to graphite, allowing ferrite to preferentially form in the region adjacent to the graphite spheres.

[0088] The higher Si content strengthens the ferrite through solid solution, allowing the ferrite to maintain a certain strength while playing a role in plasticity buffering; Cu inhibits excessive ferritification in the matrix region between graphite spheres, allowing this region to maintain a higher proportion of pearlite.

[0089] This results in a spatial structure where the region adjacent to the graphite is relatively enriched with ferrite, while the region between the graphite spheres is relatively enriched with pearlite. The ferrite near the graphite spheres can alleviate stress concentration at the graphite-matrix interface, delaying crack initiation and propagation; the pearlite between the graphite spheres constitutes the main load-bearing area, enabling the cast traction wheel to maintain high strength and hardness.

[0090] The above-mentioned organizational regulation also improves the consistency between different sections of the traction wheel. The spoke 42 section is relatively thin and cools faster, and in-flow inoculation can increase the number of effective nuclei and reduce the tendency of free carbide formation; the rim 41 and hub 43 sections are relatively thick, and iron mold sand covering conditions can shorten their solidification time and inhibit graphite coarsening and solidification segregation.

[0091] The upper and lower coated sand shells are prepared in the same direction using two sand box shell-making units 1. By controlling the time difference in shell-making completion and the temperature difference at corresponding positions, the difference in the initial cooling boundaries on both sides of the traction wheel casting 4 along the axial direction can be reduced. Combined with the transition cooling after unpacking, the differences in microstructure and hardness of the rim 41, spokes 42, hub 43, and both sides along the axial direction are further reduced.

[0092] This invention enables the graphite nucleation and distribution state formed in the eutectic stage to further influence the carbon migration and matrix transformation path in the eutectoid stage, forming an eutectoid path adjustment driven by nucleation density, thereby achieving both strength, plasticity and uniformity of properties in multiple parts without overall heat treatment.

[0093] like Figure 2 As shown in (a), the traction sheave casting 4 includes a rim 41 located on the radial outer periphery, a hub 43 located in the central region, and spokes 42 connecting the rim 41 and the hub 43. The traction sheave casting 4 has an axial center surface 44 at the middle of its axial width.

[0094] The outer periphery of the rim 41 is provided with a traction rope groove for engaging with the traction rope. Figure 2 The number of traction rope grooves shown is only used to indicate the outer peripheral working surface of the rim 41, and is not used to limit the actual number of traction rope grooves installed on the traction wheel.

[0095] Metallographic sampling positions 45, 46, and 47 are respectively set on the rim 41, spokes 42, and hub 43.

[0096] Metallographic sampling position 45 for the rim is located at the middle of the effective load-bearing section thickness of the rim 41; metallographic sampling position 46 for the spokes is located at the middle of the thickness of the spokes 42, avoiding the transition area between the spokes 42 and the rim 41 and hub 43; metallographic sampling position 47 for the hub is located at the middle of the effective wall thickness of the hub 43 outside the shaft hole. All metallographic sampling positions avoid gating and riser remnants, surface oxide layers, and areas significantly affected by machining.

[0097] At the metallographic sampling positions 45 (rim), 46 (spoke), and 47 (hub), the graphite spheroidization rate was not less than 90%, the number of graphite spheres was 160–300 per mm², and the free carbide area fraction was not higher than 0.5%.

[0098] The term "average" here means that the metallographic sampling positions 45 (rim), 46 (spoke), and 47 (hub) independently meet the same criteria, and does not mean that the test results of the three sampling positions are combined and then averaged.

[0099] The graphite spheroidization rate and graphite spheroid count were statistically analyzed on unetched metallographic specimens. The graphite spheroidization rate was determined according to the general metallographic testing method for ductile iron. The graphite particles used for the statistics of graphite spheroid count and graphite adjacent areas refer to graphite particles that are included in spherical or near-spherical graphite according to the corresponding metallographic testing method, and whose equivalent diameter is not less than 10 μm.

[0100] The equivalent diameter refers to the diameter of a circle with the same projected area as the corresponding graphite particle. Graphite particles located at the edge of the metallographic field of view and whose outer contours cannot be completely determined are not included in the statistics of graphite spheres and adjacent graphite regions.

[0101] Free carbides refer to carbides in the metallographic structure that exist as independent carbide phases or eutectic carbides, excluding cementite in pearlite lamellars. The area fraction of free carbides is based on the area of ​​the metallographic region after deducting graphite, porosity, and non-metallic inclusions.

[0102] At the metallographic sampling positions 45 (rim), 46 (spoke), and 47 (hub), the area fraction of pearlite in the matrix is ​​75%–90%, and the total area fraction of other matrix components besides pearlite and ferrite is no more than 5%, with the remainder being ferrite.

[0103] The area fractions of pearlite, ferrite, and other matrix structures are based on the area of ​​the matrix region formed after further subtracting free carbides from the aforementioned metallic structure regions.

[0104] When the pearlite area fraction is less than 75%, the strength and hardness of the traction sheave may be insufficient; when the pearlite area fraction is greater than 90%, the space for ferrite to form around the graphite spheres is significantly reduced, which is not conducive to improving the elongation after fracture and alleviating stress concentration at the graphite-matrix interface.

[0105] The spatial distribution of graphite adjacent area and matrix structure of metallographic samples obtained from metallographic sampling positions 45, 46, and 47 of wheel hub were statistically analyzed.

[0106] Based on statistically valid graphite spheres, a corresponding graphite neighborhood is formed by extending 10 μm outward from the boundary of each graphite sphere. The area of ​​the graphite sphere itself is not included in the graphite neighborhood.

[0107] When the outer expansion regions of adjacent graphite spheres overlap, the combined region after the overlap is taken as the graphite neighboring region, and the overlapping part is not counted twice in the region area and the ferrite area therein.

[0108] Graphite spheres located at the edge of the metallographic field of view and whose outer contours or extended regions cannot be fully defined are not included in the statistics of graphite adjacent regions. Graphite particles that are obviously irregular and not counted as spherical or near-spherical graphite are also not used to form graphite adjacent regions.

[0109] At least five non-overlapping representative fields of view are selected at the same metallographic sampling location, with a cumulative effective statistical area of ​​not less than 1 mm². During the statistical process, the boundaries of graphite spheres can be identified first in the unetched state, and then ferrite and pearlite can be identified in the etched state. The relative positions of each microstructure and graphite spheres are determined by image registration.

[0110] The proportion of the ferrite area in the graphite neighborhood to the total ferrite area in the corresponding metallographic sampling location is calculated as the ratio of the sum of the ferrite areas in the graphite neighborhood in each statistical field of view to the sum of the total ferrite areas in each statistical field of view.

[0111] At the metallographic sampling positions 45 (rim), 46 (spoke), and 47 (hub), the ferrite area in the graphite-adjacent region accounts for more than 60% of the total ferrite area in the corresponding metallographic sampling positions.

[0112] The matrix region outside the graphite adjacency region refers to the region formed after further subtracting the graphite adjacency region from the matrix region. The proportion of the pearlite area outside the graphite adjacency region to the area of ​​this region is calculated as the ratio of the pearlite area outside the graphite adjacency region to the matrix region area outside the graphite adjacency region.

[0113] In the metallographic sampling positions 45 (rim), 46 (spoke), and 47 (hub), the proportion of pearlite area to the corresponding matrix area in the matrix area outside the graphite adjacent area is not less than 80%.

[0114] The overall pearlite area fraction is used to define the overall composition of the matrix structure, while the ferrite area ratio in the graphite adjacency region and the pearlite area ratio outside the graphite adjacency region are used to define the spatial distribution of ferrite and pearlite relative to graphite spheres. The two reflect different microstructure characteristics.

[0115] The as-cast high-strength and high-toughness ductile iron traction wheel prepared by the above method has a tensile strength of not less than 900 MPa and an elongation after fracture of not less than 6.0%.

[0116] The tensile strength and elongation after fracture are based on the test results of tensile specimens obtained from specified positions on the traction wheel body. The tensile specimens are taken from the middle of the thickness of the effective bearing section of the rim 41 or other body positions that can represent the main bearing section of the traction wheel, avoiding gating and riser residues, surface oxide layers and obvious casting defects.

[0117] Cast-in-place test blocks can be used for production process control and batch performance evaluation, but the test results of cast-in-place test blocks are not the sole basis for determining the tensile properties of the traction wheel body.

[0118] like Figure 2 As shown in (b), a wheel rim hardness testing area 48a, a wheel spoke hardness testing area 48b, and a wheel hub hardness testing area 48c are respectively set on the wheel rim 41, wheel spoke 42, and wheel hub 43. Figure 2 In (b), the solid test points represent the effective test points used to calculate the average hardness within each hardness test area, and the dashed boxes represent the range of the corresponding hardness test area.

[0119] At least three valid measuring points were selected in each of the wheel rim hardness testing areas 48a, 48b, and 48c, and the average Brinell hardness of the corresponding hardness testing areas was calculated. The average Brinell hardness of each hardness testing area was 245–280 HBW 10 / 3000.

[0120] The difference between the maximum and minimum average Brinell hardness values ​​in the rim hardness test area 48a, spoke hardness test area 48b, and hub hardness test area 48c is no greater than 15 HBW.

[0121] The axial center plane 44 is a central plane located in the middle of the axial width of the traction wheel casting 4 and perpendicular to the rotation axis of the traction wheel. Figure 2 (b) shows the hollow measuring point 49, which is axially symmetrical.

[0122] At least one pair of axially symmetrical measuring points 49 are provided on both sides of the axial center plane 44 on the rim 41, spokes 42, and hub 43, respectively. The same pair of axially symmetrical measuring points 49 are symmetrical about the axial center plane 44 and have the same radial position and the same depth from the corresponding axial side surface.

[0123] The Brinell hardness difference between each pair of axially symmetrical measuring points 49 is no greater than 10 HBW.

[0124] The hardness difference between the rim hardness test area 48a, the spoke hardness test area 48b, and the hub hardness test area 48c is used to reflect the consistency of cooling conditions and microstructure transformation in different cross sections; the hardness difference between each pair of axially symmetrical test points 49 is used to reflect the consistency of the preparation state of the upper and lower coated sand shells and the initial thermal state of the upper and lower iron molds.

[0125] The technical effects of the present invention will be further explained below with reference to embodiments and comparative examples.

[0126] Each group used the same specifications of traction wheel casting 4, with consistent casting dimensions, gating system, and main production equipment. Three castings were prepared for each group. The amounts of rare earth magnesium ferrosilicon alloy, ferrosilicon inoculant, and barium silicon inoculant were calculated based on the mass of the base molten iron before spheroidizing treatment.

[0127] In each embodiment, two sand box shell-making units 1 are used to prepare upper and lower coated sand shells respectively. Both sand box shell-making units 1 complete the shell-making process with the sand-shooting plate 15 above the sand box 14. After shell-making, one sand box 14 is flipped over and combined with the other sand box 14.

[0128] Each sand-shooting plate 15 is provided with a first sand-shooting hole group and a second sand-shooting hole group. The average hole diameter of the first sand-shooting hole group is larger than the average hole diameter of the second sand-shooting hole group. The first sand-shooting hole group corresponds to the shell-forming area of ​​the wheel rim 41 and the wheel hub 43, and the second sand-shooting hole group corresponds to the shell-forming area of ​​the wheel spoke 42.

[0129] The metallographic sampling locations, graphite adjacency area division, microstructure area statistics, and the setting of hardness testing areas and axially symmetrical testing points are all carried out according to the aforementioned specific implementation method. At each metallographic sampling location, no fewer than 5 non-overlapping representative fields of view are selected, with a cumulative effective statistical area of ​​no less than 1 mm².

[0130] Tensile strength and elongation after fracture were tested using traction sheave body specimens. Traction sheaves of the same specification used the same sampling location, sampling direction, and specimen size. The tensile properties and hardness of each part in the table are the average values ​​of the test results for each group of three traction sheaves; the microstructure data are the statistical range of all test results obtained from the metallographic sampling locations 45 (rim rim, spoke, and hub) for the three traction sheaves.

[0131] After the traction wheels are removed from the sand, they are allowed to cool naturally to room temperature without undergoing any subsequent heat treatment aimed at altering the overall matrix structure.

[0132] Example 1: The Si content in the base molten iron before spheroidization treatment was 3.25%.

[0133] The spheroidizing treatment uses a rare earth magnesium-silicon-iron alloy with the following mass composition: Mg 7.0%, RE 1.2%, Ca 1.6%, Si 42.0%, Al 0.6%, with the balance being Fe and unavoidable impurities; the amount added is 0.84% ​​of the mass of the base molten iron.

[0134] The inoculant used in the package is ferrosilicon, with the following composition by mass: Si 75.0%, Ca 0.7%, Al 0.5%, and the balance being Fe and unavoidable impurities; the amount added is 0.20%, and the particle size is 1-4 mm.

[0135] The in-flow inoculation method uses a barium silicon inoculant with the following composition by mass: Si 72.0%, Ba 3.0%, Ca 1.0%, Al 1.0%, with the balance being Fe and unavoidable impurities; the amount added is 0.08%, and the particle size is 0.2–0.8 mm. The barium silicon inoculant accounts for 28.6% of the total actual mass of the two inoculants added.

[0136] The temperature of the iron mold during shell making is 220℃, and the thickness of the coated sand layer is 6.0mm. The time difference between the completion of shell making in the two sand box shell making units 1 is 1.5min. The maximum temperature difference between the corresponding temperature measurement positions of the upper and lower sand boxes 14 before the boxes are closed is 8℃. The time from the completion of the box closure to the start of pouring is 2.5min.

[0137] The superheat treatment temperature of the base molten iron is 1545℃, the tapping temperature is 1505℃, and the pouring temperature is 1410℃. The time from the start of adding the barium silicon inoculant to the completion of pouring is 40 seconds.

[0138] After pouring, keep the mold closed for 13 minutes, then open the mold and temporarily stop the sand falling, allowing the coating sand layer still attached to the surface of the traction wheel casting 4 to continue cooling with the casting for 5 minutes, then perform sand falling and allow it to cool naturally.

[0139] The Si content in the resulting ductile iron was 3.75%, which was 0.50 percentage points higher than that in the base molten iron before spheroidizing treatment.

[0140] Example 2: The basic process of Example 2 is the same as that of Example 1, except that the following parameters are used: The Si content in the base molten iron before spheroidization treatment was 3.10%.

[0141] The rare earth magnesium silicon iron alloy contains 6.5% Mg, 0.8% RE, 1.0% Ca, 45.0% Si, and 0.8% Al, with an addition amount of 0.95%.

[0142] The ferrosilicon inoculant contains 80.0% Si, 0.5% Ca, and 0.8% Al, with an addition amount of 0.24% and a particle size of 1–4 mm.

[0143] The barium silicon inoculant contains 75.0% Si, 2.0% Ba, 0.5% Ca, and 1.5% Al, with an addition amount of 0.10% and a particle size of 0.2–0.8 mm. The barium silicon inoculant accounts for 29.4% of the total actual mass of the two inoculants added.

[0144] The temperature of the iron mold during shell making is 205℃, and the thickness of the coated sand layer is 5.0mm. The time difference between the completion of shell making in the two sand box shell making units 1 is 2.5min, the maximum temperature difference between the corresponding temperature measurement positions is 13℃, and the time from the completion of mold assembly to the start of pouring is 3.5min.

[0145] The superheat treatment temperature of the base molten iron is 1535℃, the tapping temperature is 1490℃, and the pouring temperature is 1405℃. The time from the initial addition of the barium silicon inoculant to the completion of pouring is 30 seconds.

[0146] After pouring, keep the iron mold closed for 11 minutes. After opening the iron mold, retain the attached coated sand layer and continue cooling for 3 minutes before removing the sand.

[0147] The Si content in the resulting ductile iron was 3.70%, which was 0.60 percentage points higher than that in the base molten iron before spheroidizing treatment.

[0148] Example 3: The basic process of Example 3 is the same as that of Example 1, except that the following parameters are used: The Si content in the base molten iron before spheroidization treatment was 3.25%.

[0149] The rare earth magnesium silicon iron alloy contains 7.5% Mg, 1.5% RE, 2.0% Ca, 42.0% Si, and 0.5% Al, with an addition amount of 0.92%.

[0150] The ferrosilicon inoculant contains 75.0% Si, 1.0% Ca, and 0.5% Al, with an addition amount of 0.24% and a particle size of 1–4 mm.

[0151] The barium silicon inoculant contains 72.0% Si, 4.0% Ba, 1.5% Ca, and 1.0% Al, with an addition amount of 0.10% and a particle size of 0.2–0.8 mm. The barium silicon inoculant accounts for 29.4% of the total actual mass of the two inoculants added.

[0152] The temperature of the iron mold during shell making is 235℃, and the thickness of the coated sand layer is 7.0mm. The time difference between the completion of shell making in the two sand box shell making units 1 is 1.0min, the maximum temperature difference between the corresponding temperature measurement positions is 6℃, and the time from the completion of mold assembly to the start of pouring is 2.0min.

[0153] The superheat treatment temperature of the base molten iron is 1550℃, the tapping temperature is 1520℃, and the pouring temperature is 1415℃. The time from the initial addition of the barium silicon inoculant to the completion of pouring is 60 seconds.

[0154] After pouring, keep the iron mold closed for 15 minutes. After opening the iron mold, retain the attached coated sand layer and continue cooling for 8 minutes before removing the sand.

[0155] The Si content in the resulting ductile iron was 3.80%, which was 0.55 percentage points higher than that in the base molten iron before spheroidizing treatment.

[0156] The final chemical composition of the ductile iron obtained in each embodiment is shown in Table 1. Carbon equivalent is calculated according to CE = C + Si / 3.

[0157] As shown in Table 1, the chemical composition, carbon equivalent, and mass ratio of residual RE to residual Mg of the ductile iron obtained in Examples 1 to 3 are all within the limits defined by this invention.

[0158] Except for the conditions that have been explicitly changed below, the remaining processes of Comparative Examples 1 to 4 are the same as those of Example 1.

[0159] Comparative Example 1: In-flow inoculation with barium silicon was eliminated, and only in-package inoculation with ferrosilicon was retained.

[0160] To minimize the impact of variations in the final Si content, the Si content in the base molten iron before spheroidization is adjusted to 3.31% during the smelting and batching stage. This Si content is determined through the furnace charge ratio, without the addition of any silicon-containing materials with inoculation effects during spheroidization or casting.

[0161] The final Si content in the resulting ductile iron was 3.75%, and the remaining major chemical components were at the same control level as in Example 1.

[0162] Comparative Example 2: After pouring, the mold was kept closed for 13 minutes, then the mold was opened and the sand was immediately dropped using vibration. No stage was set where the attached coating sand layer continued to cool with the casting.

[0163] Comparative Example 3: After pouring, the iron mold was kept closed for 20 minutes, then the iron mold was opened to allow the attached coated sand layer to continue cooling with the casting for 5 minutes before the sand was removed.

[0164] Comparative Example 4: The time difference between the completion of shell making in the two sand box shell making units 1 is 8 minutes. The maximum temperature difference between the corresponding temperature measurement positions of the upper and lower sand boxes 14 before the boxes are closed is 28℃. The time from the completion of the box closure to the start of pouring is 7 minutes.

[0165] The above three parameters are used together to determine the difference in the initial thermal state of the upper and lower iron molds and the thermal state after the molds are closed.

[0166] The tissue analysis results for the examples and comparative examples are shown in Table 2. Graphite spheroidization rate, number of graphite spheres, and pearlite area fraction are listed from minimum to maximum for all test results; free carbides and other matrix structures are listed as maximum values; the proportion of ferrite in the graphite adjacent region and the proportion of pearlite outside the region are listed as minimum values.

[0167]

[0168] As shown in Table 2, in Examples 1 to 3, the graphite spheroidization rate at the rim 41, spoke 42 and hub 43 is not less than 90%, the number of graphite spheres is between 160 and 300 per mm², and the free carbide area fraction is not higher than 0.5%.

[0169] In each embodiment, the area fraction of pearlite is between 75% and 90%, and the area fraction of other matrix structures is no higher than 5%; the proportion of ferrite in the graphite adjacent region is no less than 60% of the total ferrite area, and the proportion of pearlite outside the region is no less than 80%.

[0170] In Comparative Example 1, after the in-flow inoculation was cancelled, the number of graphite spheres and the graphite spheroidization rate decreased, while the free carbides increased, indicating that in-flow inoculation of barium silicon is beneficial to reducing inoculation decline during the transfer and waiting process of molten iron.

[0171] After the sand was immediately removed from the graphite in Comparative Example 2, the number of graphite spheres remained basically the same, but the proportion of ferrite in the graphite adjacent area decreased significantly, indicating that the transitional cooling formed by the attached coated sand layer was conducive to the formation of ferrite in the graphite adjacent area.

[0172] In Comparative Example 3, after extending the iron mold closing time, the proportion of pearlite increased, the proportion of ferrite in the graphite adjacent region decreased, while the free carbides did not increase significantly, indicating that they mainly affect the matrix structure in the eutectoid transformation stage.

[0173] The increased fluctuations in the number of graphite spheres and the proportion of pearlite at different sampling locations in Comparative Example 4 indicate that the inconsistent thermal states of the upper and lower iron molds reduce the consistency of the tissue in different parts.

[0174] The mechanical properties and hardness test results of the examples and comparative examples are shown in Table 3.

[0175] The maximum range of hardness difference in a given location refers to the maximum value of the average range of the three hardness test areas for each of the three traction sheaves in each group; the maximum value of the axial hardness difference refers to the maximum value of the hardness difference among all 49 axially symmetrical test points.

[0176]

[0177] The results of piece-by-piece testing show that the tensile strength of the traction wheels obtained in Examples 1 to 3 is not less than 900 MPa, and the elongation after fracture is not less than 6.0%; the average Brinell hardness of the three hardness test areas is between 245 and 280 HBW, the hardness range of the parts is not greater than 15 HBW, and the axial hardness difference is not greater than 10 HBW.

[0178] In Comparative Example 1, after the removal of in-flow inoculation, the tensile strength, elongation after fracture, and uniformity of hardness at different locations all decreased significantly.

[0179] In Comparative Example 2, after immediate sand removal, the elongation at break decreased and the hardness of spoke 42 increased, indicating that retaining the coated sand layer for continued cooling after unpacking is beneficial for improving plasticity and controlling local hardness.

[0180] In Comparative Example 3, after extending the mold closing time, the hardness of each part increased and the elongation after fracture decreased, indicating that an excessively long mold closing cooling time is not conducive to the coordination of strength and plasticity.

[0181] The significantly increased hardness difference and axial hardness difference in Comparative Example 4 indicate that controlling the thermal state of the upper and lower iron molds and the time from mold assembly to casting is beneficial to improving the performance consistency of different parts of the traction wheel and both sides of the axial direction.

[0182] In summary, this invention maintains an effective nucleation state when molten iron enters the mold by combining in-mold inoculation with in-flow barium silicon inoculation; it achieves staged cooling through mold closure cooling and delayed sand removal after mold opening, resulting in ferrite relatively concentrated in the graphite-adjacent region while maintaining a high pearlite proportion in the matrix outside this region; and it improves the consistency of microstructure and hardness in different parts and on both axial sides by controlling the thermal state difference between the upper and lower molds. Therefore, a cast traction wheel can achieve high strength, plasticity, and hardness uniformity without subsequent overall heat treatment.

Claims

1. A method for preparing a cast high-strength and high-toughness ductile iron traction wheel, characterized in that, Includes the following steps: The basic molten iron is prepared and smelted. A rare earth magnesium-silicon ferroalloy is used to spheroidize the molten iron, and an inoculation process is performed in the ladle using a ferrosilicon inoculant. The resulting ductile iron, by mass percentage, comprises: C: 3.15%–3.25%, Si: 3.70%–3.80%, Mn: 0.10%–0.20%, Cu: 0.70%–0.80%, residual Mg: 0.035%–0.050%, residual RE: 0.005%–0.015%, P: not more than 0.05%, S: not more than 0.025%, Sn: not more than 0.015%, Cr: not more than 0.10%, with the balance being Fe and unavoidable impurities. RE represents the total amount of rare earth elements. During the casting process, the barium silicon inoculant is added to the molten iron along with the iron flow for in-flow inoculation; The molten iron, which has been inoculated by the flow, is poured into the iron mold covered with sand. The iron mold is kept closed for 11 to 15 minutes after the pouring is completed, so that the casting can undergo the first stage of cooling in the iron mold covered with sand. After opening the mold, temporarily suspend the sand removal process, allowing the coating sand layer still attached to the surface of the casting to continue cooling for 3-8 minutes before proceeding with the sand removal and subsequent cooling.

2. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 1, characterized in that, The resulting ductile iron comprises, by mass percentage: C: 3.18%–3.22%, Si: 3.72%–3.77%, Mn: 0.12%–0.17%, Cu: 0.72%–0.77%, residual Mg: 0.038%–0.044%, residual RE: 0.006%–0.011%, P: not more than 0.035%, S: not more than 0.015%, Sn: not more than 0.010%, Cr: not more than 0.060%, with the balance being Fe and unavoidable impurities; According to the calculation based on CE = C + Si / 3, the carbon equivalent CE of the obtained ductile iron is 4.42% to 4.48%.

3. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 1 or 2, characterized in that, The mass ratio of residual RE to residual Mg in the obtained ductile iron is 0.14–0.28; The rare earth magnesium silicon ferroalloy comprises, by mass percentage: Mg: 6.5%–7.5%, RE: 0.8%–2.0%, Ca: 1.0%–2.5%, Si: 40%–45%, Al: not more than 1.0%, with the balance being Fe and unavoidable impurities; the amount of rare earth magnesium silicon ferroalloy added is 0.75%–0.95% of the mass of the base molten iron.

4. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 1 or 2, characterized in that, The Si content in the base molten iron before spheroidizing treatment is 3.05% to 3.25%. Si is introduced into the molten iron through rare earth magnesium ferrosilicon alloy, ferrosilicon inoculant used in ladle inoculation, and barium silicon inoculant used in in-flow inoculation, so that the Si content in the obtained ductile iron is 3.70% to 3.80%. The Si content in the obtained ductile iron is 0.45% to 0.70 percentage points higher than the Si content in the base molten iron before spheroidizing treatment.

5. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 1 or 2, characterized in that, The ferrosilicon inoculant used for inoculation in the package includes, by mass percentage: Si: 72%–80%, Ca: 0.5%–1.0%, Al: not more than 1.0%, with the balance being Fe and unavoidable impurities; The amount of ferrosilicon inoculant added is 0.16% to 0.24% of the mass of the base molten iron, with a particle size of 1 to 4 mm; the amount of barium silicon inoculant added is 0.07% to 0.10% of the mass of the base molten iron, with a particle size of 0.2 to 0.8 mm. The barium silicon inoculant accounts for 25% to 35% of the total mass of the ferrosilicon inoculant and the barium silicon inoculant. The time from the start of in-flow inoculation to the completion of casting is 30 to 60 seconds.

6. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 5, characterized in that, The barium silicon inoculant comprises, by mass percentage: Si: 70%–75%, Ba: 2.0%–4.0%, Ca: 0.5%–2.0%, Al: not more than 2.0%, with the balance being Fe and unavoidable impurities.

7. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 1, characterized in that, The upper and lower coated sand shells are prepared by two sand box shell-making units (1), respectively. Each sand box shell making unit (1) includes a mold (13), a sand box (14) that can be snapped into the mold (13), and a sand-shooting plate (15) set above the sand box (14). Both sand box shell making units (1) prepare coated sand shells with the sand-shooting plate (15) located above the corresponding sand box (14). After the shell is made, one of the sand boxes (14) is flipped over and then combined with the other sand box (14) so ​​that the upper and lower coated sand shells together form the casting cavity. The time difference between the completion of shell making of the two sand box shell making units (1) is no more than 3 minutes; before the shell is closed, the temperature difference between the corresponding temperature measurement positions of each group on the upper and lower sand boxes (14) corresponding to the wheel rim (41), wheel spoke (42) and wheel hub (43) is no more than 15℃; the time from the completion of the shell closure to the start of pouring is no more than 4 minutes.

8. The method for preparing a cast high-strength and high-toughness ductile iron traction wheel according to claim 7, characterized in that, Each sand-shooting plate (15) is provided with a first sand-shooting hole group and a second sand-shooting hole group. The average hole diameter of the sand-shooting hole (151) in the first sand-shooting hole group is greater than the average hole diameter of the sand-shooting hole (151) in the second sand-shooting hole group. The first sand-shooting hole group corresponds to the shell-forming area corresponding to the rim (41) and hub (43), and the second sand-shooting hole group corresponds to the shell-forming area corresponding to the spoke (42); The temperature of the iron mold during shell making is 205-235℃, and the thickness of the coated sand layer is 5-7mm; the superheating temperature of the base molten iron is 1535-1550℃, the tapping temperature is 1490-1520℃, and the pouring temperature is 1405-1415℃.

9. A cast high-strength and high-toughness ductile iron traction sheave, characterized in that, The composition by mass percentage includes: C: 3.15%–3.25%, Si: 3.70%–3.80%, Mn: 0.10%–0.20%, Cu: 0.70%–0.80%, residual Mg: 0.035%–0.050%, residual RE: 0.005%–0.015%, P: not more than 0.05%, S: not more than 0.025%, Sn: not more than 0.015%, Cr: not more than 0.10%, with the balance being Fe and unavoidable impurities. RE represents the total amount of rare earth elements. At each metallographic sampling location of the traction sheave rim, spokes, and hub, the graphite spheroidization rate is not less than 90%, the number of graphite spheroids is 160–300 / mm², and the free carbide area fraction is not higher than 0.5%. At each metallographic sampling location of the traction wheel rim, spokes and hub, the area fraction of pearlite in the matrix is ​​75% to 90%, the total area fraction of other matrix structures besides pearlite and ferrite is no more than 5%, and the remainder is ferrite.

10. A cast high-strength and high-toughness ductile iron traction sheave according to claim 9, characterized in that, At each metallographic sampling location on the rim, spokes, and hub, the ferrite area within the graphite adjacency region formed by extending 10 μm outward from the boundary of each graphite sphere accounts for more than 60% of the total ferrite area at that metallographic sampling location; in the matrix region outside the graphite adjacency region, the pearlite area accounts for no less than 80% of the matrix region area; The tensile strength of the traction sheave shall not be less than 900 MPa, the elongation after fracture shall not be less than 6.0%, the average Brinell hardness of each hardness test area of ​​the rim, spokes and hub shall be 245-280 HBW 10 / 3000 and the difference between the maximum and minimum values ​​shall not be greater than 15 HBW, and the Brinell hardness difference between each corresponding test point located on both sides of the axial center plane of the traction sheave and symmetrical about the axial center plane shall not be greater than 10 HBW.